Sequence-specific interaction between the replication initiator protein of plasmid pT181 and its origin of replication. - Koepsel, R R (1986)
The replication of the pT181 plasmid is dependent on the plasmid-encoded initiator protein RepC. We have previously shown that RepC protein has sequence-specific endonuclease and topoisomerase-like activities. In this paper we demonstrate that this initiator protein has sequence-specific DNA-binding properties. Based on filter binding of plasmid restriction fragments, RepC protein specifically recognizes only the pT181 origin region. Using DNase I and neocarzinostatin "footprinting" techniques, we show that RepC protein specifically binds to a 32-base-pair sequence within the origin that is part of the initiator cistron. Using dimethyl sulfate as a chemical probe, we have identified the purine residues that interact with the initiator protein. The features of the DNA region that interacts with RepC protein include sequences with the potential to form Z DNA and/or hairpin structures. The specific DNA-protein interaction at the origin may be critical in the initiation of pT181 DNA replication by RepC protein in association with other host initiation proteins.